Kepemimpinan Jhon Calvin Yang Transformatif - Ali Matius (Sekolah Tinggi Teologi Borneo, 2023)
Abstract: Calvin is a Transformative leader who brings many changes. The liberator of the people from wrong ideas (heresy), in which he also refers to himself as the reformer, a reformed theological architect. if Luther was the soldier who launched the opening shot of the Reformation, Calvin was the main expert who consolidated the results of Protestant progress. He tried to reform not only the doctrine and organization of the church, as did Luther, but also the socio-political order in accordance with the word of God. Calvin proved that he was a